Validation of a Next-Generation Sequencing Assay Targeting RNA for the Multiplexed Detection of Fusion Transcripts and Oncogenic Isoforms. - Sussman, Robyn T.; Oran, Amanda R.; Paolillo, Carmela; Lieberman, David; Morrissette, Jennifer J. D.; Rosenbaum, Jason N. (Archives of Pathology & Laboratory Medicine, 2020)
Context.--Next-generation sequencing is a high-throughput method for detecting genetic abnormalities and providing prognostic and therapeutic information for patients with cancer. Oncogenic fusion transcripts are among the various classifications of genetic abnormalities present in tumors and are typically detected clinically with fluorescence in situ hybridization (FISH). However, FISH probes only exist for a limited number of targets, do not provide any information about fusion partners, cannot be multiplex, and have been shown to be limited in specificity for common targets such as ALK. Objective.--To validate an anchored multiplex polymerase chain reaction--based panel for the detection of fusion transcripts in a university hospital--based clinical molecular diagnostics laboratory. Design.--We used 109 unique clinical specimens to validate a custom panel targeting 104 exon boundaries from 17 genes involved in fusions in solid tumors. The panel can accept as little as 100 ng of total nucleic acid from PreservCyt-fixed tissue, and formalin-fixed, paraffin-embedded specimens with as little as 10% tumor nuclei. Results.--Using FISH as the gold standard, this assay has a sensitivity of 88.46% and a specificity of 95.83% for the detection of fusion transcripts involving ALK, RET, and ROS1 in lung adenocarcinomas. Using a validated next-generation sequencing assay as the orthogonal gold standard for the detection of EGFR variant III (EGFRvIII) in glioblastomas, the assay is 92.31% sensitive and 100% specific. Conclusions.--This multiplexed assay is tumor and fusion partner agnostic and will provide clinical utility in therapy selection for patients with solid tumors.